Wayang Kulit Cirebon: Warisan Diplomasi Seni Budaya Nusantara - Moh. Isa Pramana Koesoemadinata (ITB Journal Publisher, LPPM ITB, 2013)
The wayang kulit (shadow puppet) theatre is a traditional art form that has thrived in Southeast Asia for a long time. In Indonesia, Malaysia and Thailand, apart from local stories, wayang kulit presents Indian epics, such as the Ramayana and Mahabharata, as a medium for Hindu-Buddhist teachings. When Islam spread in this region, the Javanese and Malay wayang kulit still kept developing, even when it was being repurposed for Islamic preaching. In its development in the Islamic era, the Javanese wayang kulit incorporated the role and influence of Sufi scholars and local rulers. The visual form, composition, and creation of the wayang kulit puppets along with the prose and musical arrangements were directly inspired by the Wali Sanga (Nine Apostles) and the following Javanese kings themselves. This paperng Kulit of Cirebonural Diplomacy of Nusantara ion in the pasteration, presents the historic wayang kulit of Cirebon and discusses its unique visual features, which reflect acculturation between ethnicities (Javanese, Chinese) as well as beliefs (local animism, Hindu-Buddhism, Islam). The historic wayang kulit of Cirebon proved that a peaceful, cross-cultural and religious diplomacy took place through the medium of art since the early stages of deployment of Islam in Java. This traditional art is a legacy for current and future younger generations, not only because of the aesthetical aspect, but also as a cross-cultural diplomacy strategy and philosophy that must be acknowledged, understood, and practiced. In accordance with the meaning of the word, 'wayang' (reflection) reflects a successful diplomacy of the past that can potentially be applied in the present, hoping harmonic relationships can emerge from cultural diversity in the midst of rapid globalization.